2017
DOI: 10.1177/2309499017690317
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between anatomy of the scapula and the incidence of rotator cuff tear and glenohumeral osteoarthritis via radiological study

Abstract: The AGA method of measurement is an excellent predictive parameter for diagnosing RCT and GHOA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…Although the above studies supported an association between a decreased CSA and the development of osteoarthritis, we are not aware of any prospective studies that have suggested causation 6,22,25,28,30,31 . It is believed that as the CSA decreases, forces on the deltoid shift, causing the forces on the glenohumeral joint to become more compressive, thereby resulting in higher loading of the cartilage and subsequent osteoarthritis.…”
Section: Shoulder Osteoarthritis and Csamentioning
confidence: 84%
See 4 more Smart Citations
“…Although the above studies supported an association between a decreased CSA and the development of osteoarthritis, we are not aware of any prospective studies that have suggested causation 6,22,25,28,30,31 . It is believed that as the CSA decreases, forces on the deltoid shift, causing the forces on the glenohumeral joint to become more compressive, thereby resulting in higher loading of the cartilage and subsequent osteoarthritis.…”
Section: Shoulder Osteoarthritis and Csamentioning
confidence: 84%
“…Additionally, both Moor et al and Heuberer et al demonstrated that the combined risk factors of age and CSA were highly predictive of degenerative rotator cuff tears 25,26 . Multiple subsequent studies have reaffirmed this relationship between a CSA of .35°and the incidence of atraumatic rotator cuff tears 22,24,[28][29][30][31] .…”
Section: Critical Shoulder Anglementioning
confidence: 87%
See 3 more Smart Citations